Activities of the summer party of the 26th Japanese Antarctic Research Expedition in 1984-1985 - Sadao Kawaguchi (National Institute of Polar Research, 1986)
The summer operations of the 26th Japanese Antarctic Research Expedition (JARE-26) in 1984-1985 are reviewed. The icebreaker SHIRASE, carrying 48 expedition members led by the present author, 7 Japanese observers, 2 Chinese scientists and 760t of cargo, left Tokyo on 14 November 1984. After calling at Fremantle in Western Australia, the ship reached Breid Bay on 19 December, and the transportation of 80t of cargo and the construction of a new observation camp (Asuka Camp) were continued until 31 December. The ship was brought to Syowa Station on 4 January 1985,and the transportation of 680t of cargo by means of helicopters was completed by 16 January. After the accomplishment of field work in the Syowa Station area, SHIRASE was brought again to Breid Bay and the field party of the Sor Rondane Mountains was picked up by her. Then the ship left the Antarctic on 2 March and returned to Tokyo via Port Louis and Singapore on 20 April. As field activities, the geological, geomorphological and geodetic surveys were carried out in the Sor Rondane Mountains during about 40 days from January to February, and the geochemical studies of the lake water in the vicinity of Syowa Station were carried out. Scientific activities on shipboard were largely the continuation from previous years; oceanographic observations and ionospheric observation were carried out throughout the voyage, and biological researches were made in the ice area as part of the international "Biological Investigations of Marine Antarctic Systems and Stockes (BIOMASS)" program.